Effectiveness of Group Counseling Services Using Self-Management Techniques to Reduce Online Game Addiction - Juni Fernando Silalahi; Mami Hajaroh; Nur Azizah (Journal of Educational Science and Technology (EST), 2024)
The aim of this research is to determine the effectiveness of group counseling services with self-management techniques to reduce online game addiction at SMA Negeri 4 Malinau. This type of research is quantitative research with experimental methods. This research design is one group pre-test-post-test. The population of this research was 32 students and the sample was 5 students. Research analysis used the Wilcoxon test with the help of SPSS 26 for Windows. Based on the results of this study, it shows a decrease in reducing online game addiction after participating in the self-management technique group counseling services that have been provided. This pretest obtained a score of 360 with an average score of 72. After being given the service, students experienced a decrease in their score on the posttest of 252 with an average of 50.4. The results of the Wilcoxon test using SPSS 26 showed that the Z count in the experimental class was -2.023 and a significance level of 0.05. It is known that the Asymp.Sig.(2-tailed) value is 0.043<0.05, so Ho is rejected and Ha is accepted. Thus, it can be concluded that self-management technique group counseling services are effective in reducing online game addiction.